Evaluation of Ibuprofen Release from Gelatin /Hydroxyapatite /Polylactic Acid Nanocomposites: Ibuprofen Release from Gelatin /Hydroxyapatite /Polylactic Acid Nanocomposites - Zohre Nabipour; Mohammad Sadegh Nourbakhsh; Mohammad Baniasadi (Iranian Journal of Pharmaceutical Sciences, 2018)
Gelatin-hydroxyapatite-polylactic acid (PLA) nanocomposites were synthesized using five different formulations. The nanocomposites were loaded with ibuprofen and the amount of drug in the carriers was determined. X-ray diffraction (XRD) analysis was conducted before and after drug loading to ensure the presence of ibuprofen on the nanocomposites. Drug delivery was evaluated in phosphate buffered saline (PBS) solution at pH 7.4 and 37°C. The results of XRD analysis showed acceptable synthesis of hydroxyapatite and the composites, confirming the loading of ibuprofen onto the synthesized nanocarriers. The results showed that maximum drug loading (58.2%) was recorded for sample D (30% gelatin, 40% nHA and 30% PLA), and minimum loading was recorded for sample E (30% gelatin, 30% nHA and 40% PLA). The maximum percentage of drug release over the course of 72 h (95.8%) was for nanocomposite D (30% gelatin, 40% nHA and 30% PLA). The minimum percentage of drug delivery (77%) was for nanocomposite E (30% gelatin, 30% nHA, 40% PLA), which contained the maximum PLA content.